PENDAMPINGAN INOVASI NASI LIWET PADA UMKM PRODUSEN NASI LIWET SUNDA RUMAH KREATIF AGRIBISNIS - Dimas Bayu Pinandoyo; Swastono Putro Pirastyo (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Media Kreatif, 2023)
Nasi Liwet Sunda got less interest especially by young consumers. Rumah Kreatif Agribisnis forced to adopt foreign culinary to sustain the production. They need innovation to keep producing nasi Liwet. The aim of this public servive was to give an alternative of Nasi Liwet Sunda that can be accepted by young consumers. Methods that being applied for this public service were FGD and literature study. Formulation was conducted by Fusion Methods. Assistance process was held in Rumah Kreatif Agribisnis involving two experts from partner, assisted by thirteen students from Art Culinary department of Politeknik Negeri Media Kreatif. Evaluation was held using FGD method. From this assistance, two innovated Nasi Liwet Sunda was rpduced and ready to be sold.